Cochlear ablation in neonatal rats disrupts inhibitory transmission in the medial nucleus of the trapezoid body. (23rd April 2019) - Hruskova, Bohdana; Trojanova, Johana; Kralikova, Michaela; Melichar, Adolf; Suchankova, Stepanka; Bartosova, Jolana; Burianova, Jana Svobodova; Popelar, Jiri; Syka, Josef; Turecek, Rostislav
Highlights: Cochlear ablations affect inhibitory receptors and glycinergic boutons in the MNTB. A switch in presynaptic inhibitory receptors depends on cochlear activity. Auditory experience plays a role in the maturation of brainstem glycinergic circuits. Abstract: Inhibitory circuits in the auditory brainstem undergo multiple postnatal changes that are both activity-dependent and activity-independent. We tested to see if the shift from GABA- to glycinergic transmission, which occurs in the rat medial nucleus of the trapezoid body (MNTB) around the onset of hearing, depends on sound-evoked neuronal activity. We prevented the activity by bilateral cochlear ablations in early postnatal rats and studied ionotropic GABA and glycine receptors in MNTB neurons after hearing onset. The removal of the cochlea decreased responses of GABAA and glycine receptors to exogenous agonists as well as the amplitudes of inhibitory postsynaptic currents. The reduction was accompanied by a decrease in the number of glycine receptor- or vesicular GABA transporter-immunopositive puncta. Furthermore, the ablations markedly affected the switch in presynaptic GABAA to glycine receptors. The increase in the expression of postsynaptic glycine receptors and the shift in inhibitory transmitters were not prevented. The results suggest that inhibitory transmission in the MNTB is subject to multiple developmental signals and support the idea that auditory experience plays a role in the maturation of the brainstem glycinergic circuits.